COMPARATIVE STUDY ON GROWTH AND PHOTOSYNTHETIC PIGMENT DYNAMICS OF TWO MICROALGAE UNDER THE INFLUENCE OF WATER POLLUTION WITH THE HERBICIDE GLUFOSINATE - PLUGARU, Sebastian Radu Cristian; FODORPATAKI, Laszlo; ORBAN, Mihaela; SARB, Anca; TOMPA, Bernat; KOVACS, Balazs (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The aim of the study is to compare biochemical and physiological reactions of two related species of green microalgae (Scenedesmus acuminatus and Scenedesmus opoliensis), both considered suitable for bioindication and remediation of aquatic environments polluted with herbicides. Monoalgal axenic cultures were treated for 10 days under controlled conditions with different concentrations (from 0.1 μM to 100 µM) of glufosinate (a non-selective contact herbicide that inhibits glutamine synthase activity, thus disturbing photorespiration, inhibiting photosynthetic carbon assimilation, and generating ammonium excess in plant cells). S. opoliensis was found to be a better indicator of adverse effects of glufosinate than S. acuminatus. Changes in the ground chlorophyll fluorescence (reflecting light energy harvesting capacity), in cell division rate and in chlorophyll-a content may be early, cost-effective and sensitive markers of herbicide impact on microalgal communities inhabiting polluted water. Our results bring new data concerning the need of selection among related test organisms based on differentiated tolerance, as well as concerning biochemical parameters suitable for evaluation of water pollution impact when organic xenobiotics accumulate in aquatic environments. Thus, the presented results may be applied in optimizing bioindication of water quality using microalgae, and in treatment of wastewater polluted due to agricultural practices.